Overcoming Implementation Barriers of Concurrent Treatment for Eating Disorders and Posttraumatic Stress Disorder: Two Novel and Feasible Approaches - Kathryn Trottier; Sara Bartel; Aaron Keshen (Behavioral Sciences)
Eating disorders (EDs) and posttraumatic stress disorder (PTSD) frequently co-occur and share a functional relationship. Evidence suggests benefits of integrated and/or concurrent treatment; however, implementation is hindered by clinician training burden and the challenges of delivering two treatments simultaneously. This paper explores two novel and feasible approaches to addressing ED-PTSD. The first is a clinician-guided cognitive behavioural workbook intervention delivered concurrently with ED treatment. It involves psychoeducation, addresses dissociation, and encourages approach (versus avoidance) practices. The second involves combining Written Exposure Therapy (WET) with ED treatment at both outpatient and day hospital levels of care. Both interventions have a low training burden and are feasible in routine clinical practice, making concurrent approaches available to those who need them.